Studying Toxigenic Fungi and Mycotoxins Detection from Bean (Phaseolus vulgaris L) in Duhok Province/Kurdistan of Iraq. - Lina F. Hussein; Asia A. M. Saadullah (Zanco Journal of Pure and Applied Sciences, 2023)
The common bean (Phaseolus vulgaris L.) is one of the most widely farmed legumes, with farmers cultivating a variety of cultivar variants in Kurdistan of Iraq. Total of 50 bean samples were tested to establish their mycological contamination and their toxigenic potential under certain conditions, a variety of fungi may develop within bean grains; some of which have the capacity to synthesize mycotoxins. In current study toxigenic fungi were studied in beans (Phaseolus vulgaris L.) Aspergillus spp., Fusarium spp. and Penicillium spp. were the most frequently isolated genera, followed by Phoma sp., Mucor spp., Alternaria spp., Curvularia spp., Rhizopus spp., Eurotium sp. Chaetomium spp, Yeasts and Drechslera spp. Among 20 Aspergillus 11 strains produced mycotoxins: 30% produced aflatoxins (AFs) ranged between 81-260 ppb; 5% produced ochratoxin A (OTA 70-100 ppb) and 26.6% of Fusarium produced Trichothecene T-2/HT-2 (50- 94 ppb). The toxigenic species were A. flavus, A. parasiticus, A. ochraceus, A. carbonarius A. niger and F. sporotrichioides.